2013
DOI: 10.1186/1472-684x-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and attitudes toward palliative care in Northern Ireland

Abstract: BackgroundThe World Health Organisation recognises palliative care as a global public health issue and this is reflected at strategic level. Despite this, palliative care may not be universally welcomed. Surveys over the last decade have suggested that the general public have a lack of knowledge and negative perceptions towards palliative care. A detailed and comprehensive understanding of public views is needed in order to target education and policy campaigns and to manage future needs, expectations and reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
159
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(184 citation statements)
references
References 14 publications
(15 reference statements)
16
159
7
2
Order By: Relevance
“…However, there are some similarities in challenges to PC provision. The main common obstacles to the provision of PC in both developed countries and LMICs include lack of a properly trained workforce [41,[56][57][58], fear among HCPs [106,107], lack of awareness about PC [59,60,[108][109][110], limited funding and lack of coordination amongst services [106]. However, in developing countries, factors affecting the provision of PC services to cancer patients further include lack of resources and inadequate physical infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some similarities in challenges to PC provision. The main common obstacles to the provision of PC in both developed countries and LMICs include lack of a properly trained workforce [41,[56][57][58], fear among HCPs [106,107], lack of awareness about PC [59,60,[108][109][110], limited funding and lack of coordination amongst services [106]. However, in developing countries, factors affecting the provision of PC services to cancer patients further include lack of resources and inadequate physical infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…However, challenges include the lack of infrastructure and backup support for hospice care at home (Cheng, Chen, & Chiu, ). Moreover, aside from the problems of the accessibility and availability of hospice resources, a lack of knowledge and limited public awareness about the concept of a hospice can reduce its penetration (McIlfatrick et al, ; Seymour, ). A cross‐sectional survey found that individuals with a high education level, strong social ties, family‐oriented personality and group‐focused values are likely to have better hospice knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…When physicians in television medical dramas do discuss palliative care this may raise public awareness by providing education about for example preferences regarding end-oflife care and the possibility of shared-decision making. Video-based tools are found to be effective in improving patient knowledge about ACP and palliative care [30] and were even used in large-scale national campaigns, such as Dying Matters [31] to increase public awareness about end-of-life care [32]. In the television medical dramas words as "death" and "dying" were regularly used and in this respect the television medical dramas contribute to normalizing the use of these words.…”
Section: Communicationmentioning
confidence: 99%